Extraction and X-ray Diffraction Studies on Starches of Forest Origin - Rani, Abha; Chawhaan, Pravin H.; Rathore, Mala (Indian Forester, 2010)
Starch is the principal carbohydrate photosynthesized by means of solar energy. It is produced by all green plants and is basically found in the seeds, fruits, tubers, roots and stems of various plants, notably in corn, potatoes, wheat and rice. Starch varies widely according to its source owing to its granular characteristics. Curcuma angustifolia Roxb. (Tikhur) and Curculigo orchioides Gaertn. (Kalimusli), two important medicinal plants, contains starch in its rhizome and root stock. Starch from these species was isolated, purified and yield of starch was found 37.64 % in C. angustifolia and 11.56 % in C. orchioides. The X-ray diffraction pattern of C. angustifolia starch, exhibited 6 peaks at reflection angle 14.2° , 17.2° , 19.4° , 22.15° , 24.2° and 26.2° . Of these 6 peaks, one peak at reflection angle 17.2 was strong, 4 peaks at reflection angle 14.2° , 17.2° , 19.4° , 22.15° , 24.2° were medium and one peak at reflection angle 26.2° was weak. In C. orchioides,9 peaks at reflection angle 11.5° , 14.8° , 15.2° , 16.8° , 18.1° , 23.4° , 24.3° , 26.7° and 27.9° were obtained. Of these 9 peaks, 4 peaks at reflection angle 14.8° , 15.2° , 16.8° , 18.1° , 24.3° were strong, 1 peak at reflection angle 23.4° was medium and 3 peaks at reflection angle 26.7° , 27.9° and 11.5° were weak. The starch pattern in C. angustifolia resembles with the 'B' pattern of potato starch and that of C. orchioides resembles with the 'A' pattern of corn starch. From the results, it can be concluded that Curcuma angustifolia and Curculigo orchioides starches could become alternatives for food developers.